A Single Amino Acid Substitution in Structural Protein VP2 Abrogates the Neurotropism of Enterovirus A-71 in Mice - Yeo, Huimin; Chong, Connie Wan Hui; Chen, Elijah Weihua; Lim, Ze Qin; Ng, Qing Yong; Yan, Benedict; Chu, Justin Jang Hann; Chow, Vincent T. K.; Alonso, Sylvie (Frontiers in Microbiology, 2022)
Enterovirus 71 (EV-A71) causes hand, foot and mouth disease (HFMD) in children and has been associated with neurological complications. With no specific treatment and a monovalent vaccine limited to the Chinese market, HFMD remains a serious public health concern and an economic burden to affected societies. The molecular mechanisms underpinning EV-A71 neurovirulence have yet to be fully elucidated. In this work, we provide experimental evidence that a single amino acid substitution (I to K) at position 149 in structural protein VP2 of a non-mouse-adapted EV-A71 strain completely and specifically abrogated its infectivity in murine motor neuron-like NSC-34 cells. We showed that VP2 I149K mutant was impaired in murine SCARB2-mediated entry step but retained the ability to attach at the cell surface. In vivo, VP2 I149K mutant was fully attenuated in a symptomatic mouse model of progressive limb paralysis. While viral titers in limb muscles were comparable to mice infected with parental wild-type strain, significantly lower viral titers were measured in the spinal cord and brain, with minimal tissue damage, therefore indicating that VP2 I149K mutant is specifically impaired in its ability to invade the central nervous system. This study highlights the key role of amino acid at position 149 in VP2 in EV-A71 neurovirulence, and lends further support that the EF loop of VP2 represents a potential therapeutic target.